FUNDAMENTAL APPROACHES TO THE FINANCIAL AND ECONOMIC ASSESSMENT OF INVESTMENT PROJECTS (Scientific Journal of Actuarial Finance and Accounting, 2025)
This article examines the fundamental methodologies for the financial and economic assessment of investment projects. It explores a range of evaluation techniques, including discounting approaches, profitability metrics, and risk analysis, supplemented with personal insights and recommendations.